Model Augmented Reality Curriculum - Smolic, Aljosa (My University, 2020)
Augmented Reality (AR) is a rapidly growing field in information and communication technologies, drawing increasing numbers of professionals. Higher education institutions, however, are struggling to keep abreast of its development and to train specialists quickly, providing few courses which sufficiently align with the needs of industry. In addition to this, the field is developing so rapidly that existing courses struggle to keep pace. They also often focus too narrowly on specifics to allow for the building of the formative foundations of AR education. This paper aims to address this need by proposing a blueprint curriculum in Computer Science Education for teaching AR in universities at two levels, foundations and advanced. To begin, we survey the state of the art, identifying common needs and problems in existing courses which focus on AR. We then detail a skills framework comprised of 12 groups of skills suitable to meet industry needs, and built upon it two model lesson plans for a foundation and an advanced course. We conclude with a discussion of assessment techniques and curricular design options of embedding such coursework into existing academic programs and a forecast of the future of this academic field.
ITiCSE-WGR '20: Proceedings of the Working Group Reports on Innovation and Technology in Computer Science Education Association for Computing Machinery, New York, United States, Trondheim Norway , 2020, ISBN: 978-1-4503-8293-9.
Keywords: Software Engineering; Augmented Reality; Curriculum; Creative Technologies; Digital Engagement; Computer Education/Literacy; Information technology in education; Multimedia & Creativity; Other